Curriculum Renewal for Interprofessional Education in Health : National Audit Project Resource Booklet. (Office for Learning and Teaching, 2014)
This is resource booklet emanating from a project that responded to the urgent need for curriculum renewal in higher education health education - in particular, the need to graduate students from all health professions with well-developed interprofessional practice (IPP) capabilities. IPP capabilities are identified as essential for delivering health services that are safer, more effective, and more sustainable. The resource booklet presents the results of a national audit survey - templates used and implementation case studies.